Hypothermic and Low-Temperature Storage of Garlic (Allium sativum L.) for in Vitro Collections - Ivchenko, Tetyana V.; Vitsenya, Tatyana I.; Shevchenko, Nadiya A.; Bashtan, Natalia O.; Kornienko, Sergiy I. (Problems of Cryobiology and Cryomedicine, 2017)
New methods to establish various types of plant genetic collection are developed in Ukraine in order to preserve the existing species and varieties. This research deals with the effects of short-term hypothermic (4Â°C) and long-term low temperature (â€“196Â°C) storage on viability of the collection samples of garlic (Allium sativum L.). In the first case the culture of garlic sprout of Duchess variety was stored in vitro at the temperature of 4Â°C in the Murashige-Skoog (MS) medium with different mineral composition (1/2 MS and MS) in the dark for 3, 6, 9 and 12 months as well as in MS medium with various concentrations of sucrose (4.5, 6, 9 and 12%) at 22Â°C. The material for long-term low temperature storage of the garlic samples in liquid nitrogen were the meristems of different development type, Duchess (winter) and Manuilivskyy (spring) varieties. The apices were dehydrated in plant vitrification solution (1 M sucrose + 2 M glycerol + 2.5 M ethylene glycol) for 120 min, placed into cryovials and immersed into liquid nitrogen. The samples were stored at the temperature of â€“196Â°C for 5 years. The storage at 4Â°C in 1/2 MS medium provided the maximum preservation of the regenerated plants during a year (94.4%). During culturing at 22Â°C the highest viability (85%) was observed in the medium, containig 12% sucrose. Long-term storage of garlic meristem at â€“196Â°C did not affect the viability and growth rate if compared to the apices, thawed an hour after plunging into liquid nitrogen. The viability of vitrified-warmed garlic meristems of Duchess and Manuilivskyy varieties was about 60%. Â Probl Cryobiol Cryomed 2017; 27(2): 110â€“120<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />